Clinical significance of CDH13 promoter methylation as a biomarker for bladder cancer: a meta-analysis. Issue 1 (December 2016) - Chen, Feng; Huang, Tao; Ren, Yu; Wei, Junjun; Lou, Zhongguan; Wang, Xue; Fan, Xiaoxiao; Chen, Yirun; Weng, Guobin; Yao, Xuping
Abstract Background Methylation of the tumor suppressor gene H-cadherin (CDH13 ) has been reported in many cancers. However, the clinical effect of theCDH13 methylation status of patients with bladder cancer remains to be clarified. Methods A systematic literature search was performed to identify eligible studies in the PubMed, Embase, EBSCO, CKNI and Wanfang databases. The pooled odds ratio (OR) and the corresponding 95 % confidence interval (95 % CI) was calculated and summarized. Results Nine eligible studies were included in the present meta-analysis consisting of a total of 1017 bladder cancer patients and 265 non-tumor controls. A significant association was found betweenCDH13 methylation levels and bladder cancer (OR = 21.71, P  < 0.001). The results of subgroup analyses based on sample type suggested thatCDH13 methylation was significantly associated with bladder cancer risk in both the tissue and the urine (OR = 53.94, P  < 0.001; OR = 7.71, P  < 0.001; respectively). A subgroup analysis based on ethnic population showed that the OR value of methylatedCDH13 was higher in Asians than in Caucasians (OR = 35.18, P  < 0.001; OR = 8.86, P  < 0.001; respectively). The relationships betweenCDH13 methylation and clinicopathological features were also analyzed. A significant association was not observed betweenCDH13 methylation status and gender (P  = 0.053). Our results revealed thatCDH13 methylation was significantly associated with high-grade bladder cancer, multiple bladder cancer and muscle invasive bladder cancer (OR = 2.22, P  < 0.001; OR = 1.45, P  = 0.032; OR = 3.42, P  < 0.001; respectively). Conclusion Our study indicates thatCDH13 methylation may play an important role in the carcinogenesis, development and progression of bladder cancer. In addition, CDH13 methylation has the potential to be a useful biomarker for bladder cancer screening in urine samples and to be a prognostic biomarker in the clinic.